English homework for key stage 2 [ activity-based learning - McGowan, Andrea; Forster, Colin , 1926-; Parfitt, Vicki (Abingdon [England] ;New York : Routledge, 2010)
Suitable for busy teachers, this title presents a selection of 'pencil-free' activities, aligned with the National Curriculum Programmes of Study and with links to the topics set out in the PNS
Description based on print version record
Keywords: Active learning -- Great Britain; Education, Elementary -- Parent participation -- Great Britain; English language -- Study and teaching (Elementary) -- Activity program -- Great Britain; Homework -- Great Britain